High 10-year risk of cardiovascular disease in newly diagnosed Rheumatoid Arthritis (RA) patients - Maradit-Kremers, Hilal (2008)
PURPOSE: The purpose of this study was to estimate the 10-year absolute risk of CV events in newly diagnosed RA subjects and the potential contribution of CV risk factors to absolute risk assessment. METHODS: A population-based incidence cohort of RA subjects (ascertained according to ACR criteria) was assembled and compared to an age and sex-matched cohort of non-RA subjects. Data were collected on CV risk factors and CV events. Cox regression models were used to estimate the 10-year risk of a combined CV endpoint, adjusting for CV risk factors. Subjects were classified into 5 risk categories based on their 10-year absolute risk. RESULTS: The absolute CV risk in RA subjects was similar to that of non-RA subjects who were 5-10 years older. The absolute risk varied substantially according to presence of CV risk factors. The 10-year absolute CV risk among 60-69 year old RA subjects with no risk factors was 16.8% but rose to 60.4% in the presence of smoking, hypertension, dyslipidemia, diabetes and obesity. Among RA subjects with low, as compared to normal or high BMI, in addition to the above risk factors, the 10-year absolute CV risk rose to 86.2%. CONCLUSION: More than half of 50-59 year old newly diagnosed RA subjects and all of those >60 years of age had a 10% or greater risk of CV disease within the next 10 years and should be targeted for specific CV risk reduction strategies tailored to their personal risk profiles.